DAMPAK TAYANGAN IKLAN COMBANTRIN VERSI "BEBAS CACINGAN BEBAS BERMAIN" TERHADAP PERILAKU ORANGTUA UNTUK MENJAGA KESEHATAN ANAK (Survei pada Orangtua di Kelurahan Palmerah 2) - Putri Dyaningtasjah (2018)
This study discusses how the impact of Combantrine ad impressions on parental behavior to maintain the health of children in Posyandu Kelurahan Palmerah 2. The purpose of this study is to find out how much the impact of free versions of the free versions of free versions of the free versions of the free versions of the combat performance. Theory used is the theory of SOR. The research method used is survey method to know how big impact of advertisement advertisement Combantrin version of "free wormy free play" to behavior of parent to keep child health. Data collection techniques used is the dissemination of questionnaires to respondents. The total population in this study amounted to 1926 and the number of samples in this study is 95. The test results obtained correlation test of 0.687 which means have a strong relationship and the coefficient of determination of 47.2% and the remaining 52.8%. While the value of T arithmetic of 9.068> of T table of 1.661. Which means that there is an impact between Combantrine ad impressions on parental behavior to keep children healthy. The conclusion of this research is Combantrine ad impressions give impact to parental behavior with several factors. Combantrin needs to improve the uality of the combantrin ad and combantrin worm drug product itself